2005
DOI: 10.1103/physrevb.71.165439
|View full text |Cite
|
Sign up to set email alerts
|

Diameter selective reaction processes of single-wall carbon nanotubes

Abstract: A novel method is presented which allows the characterization of diameter selective phenomena in SWCNTs. It is based on the transformation of fullerene peapod materials into double-wall carbon nanotubes and studying the diameter distribution of the latter. The method is demonstrated for the diameter selective healing of nanotube defects and yield from C70 peapod samples. Openings on small diameter nanotubes are closed first. The yield of very small diameter inner nanotubes from C70 peapods is demonstrated. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2006
2006
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 24 publications
3
45
0
1
Order By: Relevance
“…Abe et al [24] reported X-ray measurements that suggest a more likely diameter difference of 0.72 nm. Even though a recent Raman analysis supports this value [25], we think that our main results are not affected by this difference. For larger equilibrium diameters the interaction will be weaker in general and therefore more likely reduce the calculated splitting.…”
Section: Discussionmentioning
confidence: 45%
“…Abe et al [24] reported X-ray measurements that suggest a more likely diameter difference of 0.72 nm. Even though a recent Raman analysis supports this value [25], we think that our main results are not affected by this difference. For larger equilibrium diameters the interaction will be weaker in general and therefore more likely reduce the calculated splitting.…”
Section: Discussionmentioning
confidence: 45%
“…Using the method detailed above, we have calculated the inhomogeneous broadening of the RBM frequency of the (10,0), (7,4), and (5,5) SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Long range force constants were taken into account to ensure high accuracy of the frequencies: the length of the supercells used to calculate the Hessian matrices were 12.7 Å, 13.6 Å, and 14.7 Å for (10,0), (7,4), and (5,5), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations